Management of Advanced Chronic Kidney Disease During the COVID-19 Pandemic: Suggestions From the Canadian Society of Nephrology COVID-19 Rapid Response Team. (July 2020) - White, Christine A.; Kappel, Joanne E.; Levin, Adeera; Moran, Sarah M.; Pandeya, Sanjay; Thanabalasingam, Susan J.
Purpose of program: To provide guidance on the management of patients with advanced chronic kidney disease (CKD) not requiring kidney replacement therapy during the COVID-19 pandemic. Sources of information: Program-specific documents, pre-existing, and related to COVID-19; documents from national and international kidney agencies; national and international webinars, including webinars that we hosted for input and feedback; with additional information from formal and informal review of published academic literature. Methods: Challenges in the care of patients with advanced CKD during the COVID-19 pandemic were highlighted within the Canadian Senior Renal Leaders Forum discussion group. The Canadian Society of Nephrology (CSN) developed the COVID-19 rapid response team (RRT) to address these challenges. They identified a lead with expertise in advanced CKD who identified further nephrologists and administrators to form the workgroup. A nation-wide survey of advanced CKD clinics was conducted. The initial guidance document was drafted and members of the workgroup reviewed and discussed all suggestions in detail via email and a virtual meeting. Disagreements were resolved by consensus. The document was reviewed by the CSN COVID-19 RRT, an ethicist and an infection control expert. The suggestions were presented at a CSN-sponsored interactive webinar, attended by 150 kidney health care professionals, for further peer input. The document was also sent for further feedback to experts who had participated in the initial survey. Final revisions were made based on feedback received until April 28, 2020. Canadian Journal of Kidney Health and Disease (CJKHD) editors reviewed the parallel process peer review and edited the manuscript for clarity. Key findings: We identified 11 broad areas of advanced CKD care management that may be affected by the COVID-19 pandemic: (1) clinic visit scheduling, (2) clinic visit type, (3) provision of multidisciplinary care, (4) bloodwork, (5) patient education/support, (6) home-based monitoring essentials, (7) new referrals to multidisciplinary care clinic, (8) kidney replacement therapy, (9) medications, (10) personal protective equipment, and (11) COVID-19 risk in CKD. We make specific suggestions for each of these areas. Limitations: The suggestions in this paper are expert opinion, and subject to the biases associated with this level of evidence. To expedite the publication of this work, a parallel review process was created that may not be as robust as standard arms' length peer-review processes. Implications: These suggestions are intended to provide guidance for advanced CKD directors, clinicians, and administrators on how to provide the best care possible during a time of altered priorities and reduced resources.